2018
DOI: 10.1108/jta-05-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Post-terrorism image recovery of tourist destination: a qualitative approach using Fuzzy-VIKOR

Abstract: Purpose This study aims to cover issues regarding traveling to a tourist destination which has seen war and terrorism. These problems can be addressed altogether, as they are interrelated. Based on tourists’ opinions, this paper aims to focus on measures or steps that can be taken to ensure changing their perceptions about a certain destination. Design/methodology/approach This study targets tourism experts for their opinions regarding the measures most necessary to change the perceptions of tourists. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Good destination imagery facilitates tourists' travel planning. According to the results of this study, the level of involvement in watching tourism programs had a significant effect on destination imagery, meaning that the higher the level of involvement of the viewer, the higher the destination imagery, which is comparable to the findings of [39,40].…”
Section: Bsupporting
confidence: 74%
See 1 more Smart Citation
“…Good destination imagery facilitates tourists' travel planning. According to the results of this study, the level of involvement in watching tourism programs had a significant effect on destination imagery, meaning that the higher the level of involvement of the viewer, the higher the destination imagery, which is comparable to the findings of [39,40].…”
Section: Bsupporting
confidence: 74%
“…Destination imagery is a key factor in tourists' behavior during the travel decision process and destination selection [38]. When tourists have a positive image of a destination, it will encourage them to visit it [39,40]. However, the tourism resources of tourist destinations are diverse, and in addition to the developed tourist attractions, there is a wealth of tourism features that have yet to be explored, and without personal experience and understanding, much of the knowledge and joy that comes with tourism will be missed.…”
Section: Correlation Between the Degree Of Travel Program Involvement And Destination Imagerymentioning
confidence: 99%
“…Tourism is a sensitive industry [ 8 ], especially to disasters and crises [ 9 ]. Due to the growing amount of disasters, literature discussing disasters is also growing [ 2 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Safety is a major concern for tourists and people would not travel to a location believed to be unsafe (Davidoff and Davidoff (1994). Ali et al (2018) concluded that physical security is an effective measure for improvement of the destination's image.…”
Section: Customer Satisfactionmentioning
confidence: 99%